Preferential differential gene expression within the WC1.1+ γδ T cell compartment in cattle naturally infected with Mycobacterium bovis - Bhat, Sajad A.; Elnaggar, Mahmoud; Hall, Thomas J.; McHugo, Gillian P.; Reid, Cian; MacHugh, David E.; Meade, Kieran G. (Frontiers in Immunology, 2023)
Bovine tuberculosis (bTB), caused by infection with Mycobacterium bovis, continues to cause significant issues for the global agriculture industry as well as for human health. An incomplete understanding of the host immune response contributes to the challenges of control and eradication of this zoonotic disease. In this study, high-throughput bulk RNA sequencing (RNA-seq) was used to characterize differential gene expression in γδ T cellsa subgroup of T cells that bridge innate and adaptive immunity and have known anti-mycobacterial response mechanisms. γδ T cell subsets are classified based on expression of a pathogen-recognition receptor known as Workshop Cluster 1 (WC1) and we hypothesised that bTB disease may alter the phenotype and function of specific γδ T cell subsets. Peripheral blood was collected from naturally M. bovis-infected (positive for single intradermal comparative tuberculin test (SICTT) and IFN-γ ELISA) and ageand sex-matched, non-infected control Holstein-Friesian cattle. γδ T subsets were isolated using fluorescence activated cell sorting (n = 10-12 per group) and highquality RNA extracted from each purified lymphocyte subset (WC1.1 + , WC1.2 + , WC1 -and γδ -) was used to generate transcriptomes using bulk RNA-seq (n = 6 per group, representing a total of 48 RNA-seq libraries). Relatively low numbers of differentially expressed genes (DEGs) were observed between most cell subsets; however, 189 genes were significantly differentially expressed in the M. bovis-infected compared to the control groups for the WC1.1 + γδ T cell compartment (absolute log2 FC ≥ 1.5 and FDR Padj. ≤ 0.1). The majority of these DEGs (168) were significantly increased in expression in cells from the bTB+ cattle and included genes encoding transcription factors (TBX21 and EOMES), chemokine receptors (CCR5 and CCR7), granzymes (GZMA, GZMM, and GZMH) and multiple killer cell immunoglobulin-like receptor (KIR) proteins indicating cytotoxic functions. Biological pathway overrepresentation analysis revealed enrichment of genes with multiple immune functions including cell activation, proliferation, chemotaxis, and cytotoxicity of lymphocytes. In conclusion, γδ T cells have important inflammatory and regulatory functions in cattle, and we provide evidence for preferential differential activation of the WC1.1 + specific subset in cattle naturally infected with M. bovis.